2017
DOI: 10.31142/ijtsrd2454
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles by Sargassum Cinctum J. Agardh and their Potential for Seed Germination

Abstract: Nanoparticles are recognizing for their applications in various fields of medical sciences and they are also under safety concern. The effects of metals nanoparticles on environment is not yet completely known to us, but some of the study had been elaborated the toxic effects of metal nanoparticles to the environment both aquatic and terrestrial as well as human healths. So, eco-friendly green synthesized nanoparticles are now leading our interest for biosafety purpose. The aqueous solution of brown seaweed (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Antimicrobial activity: The antimicrobial activity was tested according to standard method [11,12] and with little modification [3,[14][15][16][17][18][19].…”
Section: Biosynthesis and Characterization Of Silver Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial activity: The antimicrobial activity was tested according to standard method [11,12] and with little modification [3,[14][15][16][17][18][19].…”
Section: Biosynthesis and Characterization Of Silver Nanoparticlesmentioning
confidence: 99%
“…Test on seeds germination: The seed germination potential of Abelmoschus and Raphanus with treatment of biosynthesized Silver Nanoparticles was investigated according to standard protocol [2,11,12,15,16,[19][20][21].…”
Section: Biosynthesis and Characterization Of Silver Nanoparticlesmentioning
confidence: 99%
“…So, in many present research works, seaweeds were represented as a potential source of silver nanoparticles. The several previous works on the number of marine algae which were utilized as a source of nanomaterials are Padina pavonia, Pyropia yezoensis, and Sargassum species such as Sargassum angotifolium, Sargassum muticum, Sargassum cinereum, Sargassum cinctum, Sargassum polycystum, Sargassum vulgare, Sargassum tenerrium, Sargassum wightii (Singaravelu et al, 2007;Krishnan et al, 2022;Ballesteros et al, 2022;Mohandass et al, 2013;Roy and Anantharaman, 2017;Thangaraju et al, 2012;Govindaraju et al, 2015;Kumar et al, 2012;Govinddaraju et al, 2009). The single report on Sargassum swartzii for AgNPs synthesis is given by Kala et al, (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous research showed that some seaweed had excellent activity for plant growth promotion as bio-nano-fertilizer. Such as the bio-nano-fertilizer biosynthesized by the brown seaweed Sargassum cinctum promote 80% seed germination for Abelmoschus esculentus [2], likewise Chaetomorpha antennina biosynthesized Ag-Nanoparticles promote 80% seed germination for Abelmoschus esculentus and 75% seed germination for Raphanus sativus var. longipinnatus [3], Sargassum illicifolium biosynthesized Silver Nanoparticles germinates 60% seeds of Abelmoschus esculentus and 60% seeds of Raphanus sativus var.…”
Section: Introductionmentioning
confidence: 99%
“…longipinnatus [4] and biosynthesized Silver Nanoparticles by Amphiroa anceps germinated 80% seeds of Abelmoschus esculentus and 80-85.71% seeds of Raphanus sativus var. longipinnatus [5]. In this study, we selected green algae Chlorodesmis hildebrandtii for biosynthesis of Silver Nanoparticles and its application for potential for seed germination, trying to developed the most potent Nano-bio-fertilizer for agricultural application to promote the growth and yield.…”
Section: Introductionmentioning
confidence: 99%